(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
In this thesis, future teachers will be taught to create professional creativity and skills, to approach the current educational process through new pedagogical projects, the aspects of pedagogical technology and pedagogical skills will be highlighted, and the organization of the teaching process will be their world. issues such as development of vision, relations between teacher and student, speech culture, formation of pedagogical technique skills are explained.